THE EFFECT OF HEALTH EDUCATION USING THE DEMONSTRATION METHOD ON HANDWASHING WITH SOAP (HWS) SKILLS AMONG CHILDREN - Meilinda Handayani Pasaribu (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Handwashing with soap is one of the most effective public health measures for preventing gastrointestinal and respiratory infections among children. However, despite ongoing health education efforts, many children still do not perform proper handwashing techniques. Interactive educational approaches, such as demonstration methods combined with songs, may enhance children's practical skills more effectively than conventional instruction. This study aimed to determine the effect of health education using a demonstration method on handwashing with soap skills among children in the BTN AL community, Entrop Subdistrict, South Jayapura District. A quantitative study with a one-group pretest-posttest pre-experimental design was conducted involving 20 child participants selected through total sampling. The intervention consisted of a live demonstration of the WHO six-step handwashing technique accompanied by a modified version of the children's song Naik Becak. Participants' handwashing skills were assessed before and after the intervention using the WHO Standard Hand Hygiene Observation Checklist. Data were analyzed using the Wilcoxon Signed-Rank Test. The findings demonstrated a significant improvement in children's handwashing skills following the intervention. Before receiving health education, most participants were unable to perform the recommended handwashing procedure correctly. After the intervention, 18 participants (90%) successfully demonstrated all six handwashing steps independently, while only two participants (10%) still required assistance. Statistical analysis showed a significant difference between pretest and posttest scores (p < 0.001). The study concludes that health education delivered through a demonstration method combined with a modified children's song effectively improves handwashing with soap skills among children. This approach may serve as an innovative and engaging strategy for promoting healthy hygiene behaviors in early childhood.